ANALISIS PENERAPAN MODEL FLIPPED CLASSROOM MENGGUNAKAN MEDIA VIDEO YOUTUBE DALAM MENUMBUHKAN SIKAP RELIGIUS SISWA KELAS VI PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI MI MUHAMMADIYAH BUNTU BARANA - Sri Herfiani Husain; Elihami; Misran (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to analyze the implementation of the Flipped Classroom model using YouTube videos in fostering students’ religious attitudes in Pancasila Education at MI Muhammadiyah Buntu Barana. Using a qualitative case study approach, data were collected through observation, interviews, documentation, and student reflections. The findings showed that the Flipped Classroom model promoted religious attitudes, including honesty, responsibility, tolerance, discipline, and politeness. The novelty of this study lies in the finding that religious values were internalized through students’ reflective engagement with YouTube content. Another significant finding was the emergence of digital adab (digital ethics) as part of students’ religious character. In addition, a semi-offline flipped classroom approach proved effective in a rural madrasah with limited internet access.